(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
The world changed into a word called Corona, as this pandemic is making the life struggle and we all know the struggle is inevitable. Ayurveda considers it as a ‘Janapadodhwamsa Vikara’ and this pandemic is caused by Jivanu (Micro Organism) and spreads from person to person through Sankramika. Ayurveda clearly explain that this type of pandemic diseases originates from Adharma or Pragnaparadha or Mithya Ahara Vihara or Sleshamaja Krimi resulting in the malfunctioning of Kapha Pradhana Tridosha as well as involvement of Rasavaha and Pranavaha Srotas. It can be grouped under the class of Agantuja Vikara with special reference to Bhutabhisangaja. In this type of pandemic disorders, Jwara is the first symptom that manifests with entry of Jivanu into the human body and then gradually leads to development of cough and cold. So in order to get rid of these epidemics we must have a healthy and timely diet which in turn helps in increase of immunity power (Ojas) and thereby maintains proper physiological entities which make us healthy. Ayurveda consists of extensive knowledge based on ‘Swasthasya Swastha Rakshanam’ aspect mainly involving the concept of Dinacharya, Ritucharya, Hita Ahara Sevana and Nidana Parivarjana to maintain proper healthy life. First and foremost is physical distance which helps in preventing and reducing the transmission of disease. ‘Aturasya Vikara Prasamanam’ aspect mainly involves Kapha Shamanam, Vata Anulomanam, maintaining the status of Pitta, protection of Rogi Balam as well as Jwara Shamanam and Swasa Chikitsa.